Twenty Years after Philippine Trade Liberalization and Industrialization: What Has Happened and Where Do We Go from Here - Rafaelita M. Aldaba (Philippine Institute for Development Studies (PIDS), 2013)
The paper aims to review our trade liberalization policy and its contribution to the country's industrial growth and performance. After more than twenty years of liberalization, the overall performance of the manufacturing industry has been weak, growth has been slow, and contribution to value added and employment has been limited. Total factor productivity growth declined from 1996 to 2006. The industrial structure has remained "hollow" or "missing" in the middle and medium enterprises have never seriously challenged the large entrenched incumbents. The linkages between SMEs and large enterprises have also remained limited. SMEs have continued to face competitiveness problems along with difficulties in finance and market access. Trade indicators show the heavy concentration of Philippine exports on three major products groups: electronics, garments and textiles, and auto parts. Within these major product groups, exports are highly concentrated in low value-added and labor-intensive products sectors.Our experience has shown that trade liberalization does not automatically lead to a competitive domestic market economy. Imports are effective in disciplining domestic manufacturing firms. However, to sustain the competitive gains derived from the presence of imports, the government has an important role to play particularly in creating and maintaining a competitive environment. The government needs to coordinate policies to implement continued liberalization in tandem with necessary support measures that will address the obstacles to the entry, exit, and growth of domestic firms, particularly small and medium enterprises.
Keywords: 330; trade liberalization; Philippines; Philippine manufacturing; strategic industrial policy